Modern spectroscop - Hollas, J. Michael (John Wiley & Sons, 1996)
Modern Spectroscopy is aimed at an undergraduate audience, and introduces a wide range of spectroscopies, and includes both the background theory and applications to structure determination and chemical analysis. It covers rotational, vibrational, electronic, photoelectron, and Auger spectroscopy, as well as EXAFS, and the theory of laser and laser spectroscopy. Subjects such as interferometry, supersonic jet spectroscopy, and applications of spectroscopy to astrophysics are also notable by their inclusion. New material includes a discussion of icosahedral symmetry and its relevance to the C60 molecule, the basics of charge coupled device detectors, an introduction to zero kinetic energy photoelectron spectroscopy, and simple rules for the division of the vibrations of a molecule into symmetry classes. Reformatted and designed to be user-friendly, Modern Spectroscopy provides new worked examples of calculations and other problems covering a wide variety of topics.